2015
DOI: 10.4103/0972-2327.150627
|View full text |Cite
|
Sign up to set email alerts
|

Factors delaying hospital arrival of patients with acute stroke

Abstract: Background:Low rates of thrombolysis for ischemic stroke in India and other developing countries have been attributed to delays in presentation to the hospital.Materials and Methods:A prospective study was carried out during a 12-month period ending December 2012 in the department of Neurology, Malabar Institute of Medical Sciences, Kerala, India, to look for the factors contributing to delay in hospital arrival of patients with acute stroke. Patients and or their relatives were interviewed within 48 hours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
60
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 27 publications
13
60
3
4
Order By: Relevance
“…The key question is whether such an impact on accessing healthcare affects morbidity and mortality in societies. Several studies have shown that access to healthcare correlates with disease-specific outcomes in stroke, cardiovascular diseases, acute abdominal conditions, and road traffic accidents [813]. Based on these evidences and other anecdotal reports of death and injury due to hartals, we believe that hartals have a significant impact on the health of Indian society.…”
Section: Discussionmentioning
confidence: 74%
“…The key question is whether such an impact on accessing healthcare affects morbidity and mortality in societies. Several studies have shown that access to healthcare correlates with disease-specific outcomes in stroke, cardiovascular diseases, acute abdominal conditions, and road traffic accidents [813]. Based on these evidences and other anecdotal reports of death and injury due to hartals, we believe that hartals have a significant impact on the health of Indian society.…”
Section: Discussionmentioning
confidence: 74%
“…9 Stroke patients from remote areas of the country are at greater risk of not reaching hospitals because of the suspension of public transport. 11,13 Acute stroke care in individuals suspected of having COVID-19 is of special concern. According to the Ministry of Health and Family Welfare (MoHFW) Government of India guidelines, these cases are supposed to go to designated COVIDcare government hospitals-several of them are in smaller districts and are state hospitals.…”
Section: Acute Stroke Carementioning
confidence: 99%
“…Hal tersebut selaras dengan penelitian yang dilakukan di India, yaitu pasien stroke yang mempunyai tingkat pendidikan tinggi cenderung memiliki durasi keterlambatan kedatangan di rumah sakit yang lebih singkat. 8 Tingkat pendidikan merupakan salah satu faktor independen penting pada pasien dengan pengetahuan tentang stroke yang adekuat. 14 Pengetahuan tentang gejala dan tanda stroke yang adekuat merupakan salah satu faktor independen yang berhubungan dengan kedatangan pasien stroke yang lebih awal di rumah sakit.…”
Section: Bahasanunclassified
“…Walaupun dalam penelitian sebelumnya yang dilakukan di India ditemukan bahwa jarak tempat tinggal pasien yang lebih dekat dengan rumah sakit merupakan salah satu faktor yang berhubungan dengan kedatangan pasien lebih awal di rumah sakit, tetapi pengetahuan pasien mengenai gejala dan tanda stroke merupakan salah satu faktor penting yang berpengaruh pada waktu kedatangan pasien stroke di rumah sakit. 8,15 Hasil analisis antara variabel tergantung dan variabel bebas (Tabel 3), menunjukkan bahwa tidak terdapat hubungan bermakna antara keterlambatan kedatangan pasien stroke di rumah sakit dengan penggunaan ambulans sebagai pilihan mode transportasi pasien. Hasil studi sebelumnya telah menyatakan bahwa penggunaan ambulans sebagai alat transportasi dapat menurunkan tingkat keterlambatan kedatangan pasien stroke di rumah sakit, 6 namun pengetahuan pasien akan gejala dan tanda stroke merupakan hal yang penting ketika pasien akan mengambil keputusan untuk mendapatkan pelayanan ambulans sebagai mode transportasi ke rumah sakit.…”
Section: Bahasanunclassified
See 1 more Smart Citation